Effects of Story Grammar and Socratic Seminar Instructional Strategies on Secondary School Students’ Learning Outcomes in Prose in Literature-In-English in Owerri, Nigeria (2016)
The study of Literature-in-English is aimed at the complete development of the learner with respect to literary appreciation. To achieve this goal, effective teaching and learning of drama, poetry and prose are important. The reports from public examination bodies in recent times revealed a prevailing under-achievement in the subject. This has been attributed to students‟ poor performance in and attitude to the prose genre in particular. Previous studies focused more on the use of cognitive and cooperative instructional strategies without considering the effects of text structure awareness and metacognitive instructional strategies. This study, therefore, determined the effects of story grammar and Socratic seminar instructional strategies on students‟ achievement in and attitude to prose in Literature-in-English. It also examined the moderating effects of verbal ability and learning style. Reader-response and structuralist theories provided the framework while the pretest-posttest control group quasi-experimental design with 3 x 3 x 3 factorial matrix was adopted. Participants in the study were 243 senior secondary school two (SSS II) students drawn from six purposively selected secondary schools in Owerri. Six intact classes of SSS II students were used and randomly assigned to each of treatment and control groups. Instruments used were: Prose in Literature-in-English Achievement (r = 0.88), Verbal Ability (r = 0.85) tests, Students‟ Attitude to Prose in Literature-in-English (r = 0.91), Learning Style Preference (r = 0.81) questionnaires and instructional guides. Data were analysed using Analysis of Covariance and Scheffe Post-hoc test at 0.05 level of significance. There was a significant effect of treatment on students‟ achievement in prose in Literature-in-English (F(2,215) = 3.32; 2 = 0.03). Socratic seminar instructional strategy group had the highest posttest achievement mean score (= 29.71), followed by control group (= 27.35) and story grammar group (= 26.84) respectively. Similarly, there was a significant main effect of treatment on students‟ attitude to prose in Literature-in-English (F(2,215) = 3.31; 2 = 0.03). Socratic seminar group has higher posttest mean attitude score (= 56.76) when compared to control and story grammar groups respectively. There were no significant main effects of verbal ability and learning style on students‟ achievement in and attitude to prose in Literature-in-English. The two-way interaction effect of treatment and verbal ability on students‟ achievement in prose in Literature-in-English was significant (F(4,215) = 3.57; 2 = 0.06) but not on attitude. The two-way interaction effect of treatment and learning style, verbal ability and learning style and the three-way interaction effect of treatment, verbal ability and learning style on students‟ achievement in and attitude to prose in Literature-in-English were not significant. Socratic seminar instructional strategy was effective in enhancing achievement in and attitude to prose in Literature-in-English in Owerri, Nigeria. Therefore, Literature-in-English teachers should adopt Socratic seminar instructional strategy for improved learning outcomes.